Recycling disposable cups into paper plastic composites - Mitchell,J; Vandeperre,L; Dvorak,R; Kosior,E; Tarverdi,K; Cheeseman,C (Waste Management, 2014)
The majority of disposable cups are made from paper plastic laminates (PPL) which consist of high quality cellulose fibre with a thin internal polyethylene coating. There are limited recycling options for PPLs and this has contributed to disposable cups becoming a high profile, problematic waste. In this work disposable cups have been shredded to form PPL flakes and these have been used to reinforce polypropylene to form novel paper plastic composites (PPCs). The PPL flakes and polypropylene were mixed, extruded, pelletised and injection moulded at low temperatures to prevent degradation of the cellulose fibres. The level of PPL flake addition and the use of a maleated polyolefin coupling agent to enhance interfacial adhesion have been investigated. Samples have been characterised using tensile testing, dynamic mechanical analysis (DMA) and thermogravimetric analysis. Use of a coupling agent allows composites containing 40 wt.% of PPL flakes to increase tensile strength of PP by 50% to 30 MPa. The Young modulus also increases from 1 to 2.5 GPa and the work to fracture increases by a factor of 5. The work demonstrates that PPL disposable cups have potential to be beneficially reused as reinforcement in novel polypropylene composites.